Th1/Th2 Dichotomy in Obese Women with Gestational Diabetes and Their Macrosomic Babies - A. Seck; A. Hichami; S. Doucouré; F. Diallo Agne; H. Bassène; A. Ba; C. Sokhna; N. A. Khan; A. Samb (Journal of Diabetes Research)
The aim of the study was to assess T cell differentiation and the modulation of inflammatory cytokines in obese and gestational diabetes mellitus (GDM) women and their macrosomic newborns. Hence, immediately after delivery, blood samples were collected through the mother’s arm vein and the umbilical cordon vein. Biochemical parameters measured were HbA1C, glucose, insulin, triglyceride (TG), total cholesterol (Tchol), HDL cholesterol (HDLchol), and LDL cholesterol (LDLchol). T lymphocytes were purified from the total blood with Ficoll-Paque. The mRNA expression of inflammatory markers in T cells was determined by RT-qPCR. We observed that diabetic mothers exhibited higher HbA1C, glycemia, insulinemia, TG, Tchol, HDLchol, and LDLchol levels than control mothers. Glycemia was not significantly different between macrosomic and control newborns. However, insulinemia was high in macrosomic babies. TG, Tchol, HDLchol, and LDLchol were not significantly different between macrosomic and control babies. In diabetic mothers, mRNA expression of the Th1 cell subtype was significantly increased. Th1 markers were upregulated in babies born to diabetic women than in control newborns. However, expression of two Th2 markers (GATA3 and IL-4) was not significantly different between control and GDM women and between their respective newborns. Interestingly, IL-10 mRNA expression was decreased in diabetic mothers and their offsprings. The Th1/Th2 cytokine ratio was increased in GDM obese mothers and their macrosomic newborns, suggesting a proinflammatory status in these subjects.